Divorce law in the perspective of the Quran: Solutions to the phenomenon of digital divorce and social media normative study of the principles of Ihsan and Taqwa in the contemporary talak process - Joseph Antoni; Hidayatullah Ismail (Priviet Social Sciences Journal, 2026)
The phenomenon of divorce in the digital age shows a rapid increase, especially due to the involvement of social media in the family life period which is the main trigger. Divorce that used to only occur through formal legal mechanisms now often appears in the form of a digital divorce or through a social media liaison procedure such as talaq statements through text messages, uploads on social media, or online or online communication. In this context, the Qur'an remains the main source in leading Muslims to understand the nature of a divorce, not just as a breakdown of a relationship, but as a spiritual process based on the values of ihsan and piousness. This study aims to examine the law of divorce according to the Qur'an, focusing on the values of ihsan and piety as a moral solution to a major phenomenon of divorce in the digital era. This study uses a normative approach with a thematic interpretation analysis method (maudhu'i) on divorce verses in the Qur'an, such as QS. Al-Baqarah: 229–232 and QS. At-Talaq: 1-7.